Search for universal extra dimensions in pp̄ collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Aoki, M.; Askew, A.; Åsman, B.; et al. (American Physical Society (APS), 2012)
We present a search for Kaluza-Klein (KK) particles predicted by models with universal extra dimensions (UED) using a data set corresponding to an integrated luminosity of 7.3fb -1, collected by the D0 detector at a pp̄ center-of-mass energy of 1.96TeV. The decay chain of KK particles can lead to a final state with two muons of the same charge. This signature is used to set a lower limit on the compactification scale of R -1>260GeV in a minimal UED model. © 2012 American Physical Society.